2018
DOI: 10.1016/j.envint.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal arsenic exposure, child marriage, and pregnancy weight gain: Associations with preterm birth in Bangladesh

Abstract: Reducing arsenic exposure and ending child marriage could reduce the risk of preterm birth in Bangladesh. Furthermore, enhancing nutritional support to ensure adequate weight gain during pregnancy may provide additional benefits especially for women with a history of child marriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 81 publications
1
30
0
3
Order By: Relevance
“…In this study, we observed that the effect of miR-1290 on birthweight was stronger when the arsenic concentration was higher in cord blood. In utero arsenic exposure has been associated with increased risk of preterm birth [57] and lower birthweight [27] in this population. Therefore, higher expression of miR-1290 in the placenta could potentially influence birthweight via shortened gestational age and increased arsenic toxicity.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, we observed that the effect of miR-1290 on birthweight was stronger when the arsenic concentration was higher in cord blood. In utero arsenic exposure has been associated with increased risk of preterm birth [57] and lower birthweight [27] in this population. Therefore, higher expression of miR-1290 in the placenta could potentially influence birthweight via shortened gestational age and increased arsenic toxicity.…”
Section: Discussionmentioning
confidence: 94%
“…During 2008-2011, we enrolled 1,613 pregnant women aged ≥ 18 years with an ultrasound-confirmed singleton pregnancy of ≤ 16 weeks of gestation and followed them throughout pregnancy. Details of this study, including recruitment and enrollment criteria were previously reported [25,27]. At the end of follow-up, 1,184 singleton live births were recorded after exclusions due to loss of contact before delivery (n = 99), participation withdrawal (n = 121), miscarriage (n = 132), stillbirth (n = 72), and multiple pregnancies (n = 5).…”
Section: Study Population and Subject Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early marriage is also responsible for other maternal risk factors associated with negative birth outcomes (Ikamari, 2005). Studies on how early marriage affects reproductive health revealed that early exposure to sexual life leads women more likely to have different sexually transmitted diseases, pre-term deliveries, pregnancy complications, complications during child birth and so on (Rahman et al, 2018;Kamal and Hassan, 2015). Moreover, poor adoption of family planning, low utilization of contraceptives, poor caring practice of child are also seen to be connected with early marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Lower fertility control can lead to adverse fertility outcomes such as termination of pregnancy and unplanned pregnancy (Godha et al, 2013). In another study carried out in Bangladesh to identify the association between child marriage and preterm birth considering pregnancy weight gain as mediator showed a small but statistically significant indirect effect on preterm birth (RR indirect effect = 1.02; 95% CI: 1.00,1.05) (Rahman et al, 2018). A study which was based in BDHS 2011, showed that still birth, miscarriage and pregnancy termination are significantly associated with child marriage and it was also found that 70.4 % and 23.4% women who got early marriage had still birth and pregnancy termination which were greater than that women who married after getting adult (Kamal and Hassan, 2015).…”
Section: Children Bearing and Delivering Children; A Major Consequencmentioning
confidence: 99%